Otimização da produção de lipase por fermentação em estado sólido utilizando resíduos agroindustriais e imobilização em esferas de quitosana - Silva, Mairim Dahm (2024)
Enzymes play a fundamental role in various industries, with lipases being especially important for catalyzing reactions such as triglyceride hydrolysis. This study aimed to optimize lipase production through solid-state fermentation (FES) using yeast isolated from aquatic environments, with agroindustrial residues as substrates. Yeast JC054 identified by molecular biology methods as Wickerhamiella osmotolerans, showing 100% identity with fungal sequences deposited in GenBank. Lipolytic activity confirmed in a solid medium containing olive oil and rhodamine B, obtaining an enzymatic index (EI) of 3.7. In SSF, different substrate proportions used: FSG (sunflower seed meal - 100%); FSG/RFS (soybean meal residue - 50:50); and FSG/RFT (wheat bran residue - 50:50), with humidity adjusted to 55% (pH 7 phosphate buffer and 50 mM). In enzymatic kinetics, lipolytic activity reached its maximum peak at 48 h for all tested substrates. In humidity studies, levels ranged from 50%, 55%, and 60%, where FSG reached its maximum activity at 55% (31.36 ± 0.68 U g-1), while FSG/RFS and FSG/RFT showed optimal lipolytic activity at 55% (18.44 ± 0.86 U g-1) and 50% (15.28 ± 0.64 U g-1), respectively. In enzymatic extraction analysis, extraction solutions used in a 1:5 (w/v) ratio: NaCl (15 mM), Sodium Phosphate Buffer (pH 7, 15 mM), NaCl/Tween 80 (15 mM, 0.5%), and Sodium Phosphate Buffer/Tween 80 (15 mM, 0.5%). The most effective extraction solution was composed of sodium phosphate buffer/Tween 80, extracting 88% of the enzymes present in the fermented solid. For enzymatic immobilization, chitosan beads activated with 1% glutaraldehyde used at 60, 120, and 180 min to determine the best enzyme fixation time. The best fixation time found to be 1 h with an immobilization efficiency of 29.32%. This study contributes to the development of optimized lipase production processes by FES, highlighting the importance of using agroindustrial residues as substrates and enzyme immobilization on chitosan beads as a promising strategy for industrial applications.